The Healing Power of Writing: Traumatic Memories and Recovery in Italian British Literary Narratives of WW2 (Altre Modernità, 2024)
Published over a long period of time, from the late 1960s to 2022, Italian British literary narratives continue to represent powerful testimonies of the violence and persecution that the immigrant community had to endure during World War Two. The aim of this paper is to focus on how their authors recounted their experience of trauma and how they finally overcame it: although the majority of them were writing several decades after the end of hostilities, their memories of the night of 10th June 1940, of the Arandora Star tragedy (2nd July 1940) and especially of their periods of incarceration/internment always remained vivid. Building upon a long research activity, which also entailed the discovery of the majority of Italian British narratives, this paper will mostly consider memoirs and autobiographies, while methodologically connecting them to the field of Post-Traumatic Stress Disorders (PTSD). In this way, it will not only contribute to the popularity of authors like Joe Pieri, Bernard Moscardini and Peter Ghiringhelli, but it will also show the healing power of writing in migrant contexts